The Fibrinogen γ Chain Dodecapeptide Inhibits Agonist-induced Aggregation of Rabbit Platelets and Fibrinogen Binding to Rabbit Glycoprotein IIb-IIIa - Rand, Margaret L.; Packham, Marian A.; Taylor, Desirée M.; Yeo, Erik L.; Gemmell, Cynthia H.; Patil, Sonali; Lam, Stephen C.-T. (Thrombosis and Haemostasis, 1999)
The HHLGGAKQAGDV (H12) sequence at the carboxyl termini of the γ chains and the RGD sequences in the Aα chains of human fibrinogen are potential recognition sites for the binding of soluble fibrinogen to glycoprotein IIb-IIIa (GPIIb-IIIa) on activated human platelets. Thus, addition of either H12 or RGD-containing peptides inhibits aggregation of and fibrinogen binding to human platelets. In contrast, we reported previously that RGDS had relatively little inhibitory effect on these functions of rabbit platelets. In the present study, we found that H12 inhibited ADP- and thrombin-induced aggregation of rabbit platelets in a dose-dependent manner. Specificity was demonstrated by the failure of the variant HHLGGAKQAGEV peptide to inhibit ADP-induced aggregation. Furthermore, flow cytometric analyses demonstrated that H12 inhibited the binding of FITC-fibrinogen to ADP-activated rabbit platelets in a dose-dependent manner. To examine the direct interaction of H12 with rabbit GPIIb-IIIa, we performed affinity chromatography by applying an octylglucoside extract of rabbit platelet proteins onto an affinity matrix containing the fibrinogen γ chain sequence. Proteins of ∼135 kDa and ∼95 kDa were specifically eluted by soluble H12, and the 95 kDa protein band was immunoblotted by anti-LIBS1, a monoclonal antibody against human GPIIIa. In control samples, no detectable protein from rabbit platelet lysates was eluted from an RGD affinity matrix by GRGDSP. Collectively, our results demonstrated that H12 inhibits aggregation of and fibrinogen binding to rabbit platelets by directly interacting with rabbit GPIIb-IIIa. These findings suggest that rabbit platelets would serve as a suitable thrombosis model for testing the efficacy of peptide mimetics derived from H12.
Keywords: Rabbit platelets; fibrinogen; GPIIb-IIIa; gamma chain